The Implications of Campus Closures - Kent, Daniel (International Higher Education, 2022)
Many international branch campuses, particularly those originating from the United States, have closed their doors in recent years. Understanding how institutions have accommodated students during a closure may help other campuses best serve their students even in their final days of operation.